Why Nemo matters: altruism in American animation - Westfall, David W. (Kansas State University, 2009)
This study builds on a small but growing field of scholarship, arguing that certain nonnormative behavior is also non-negative, a concept referred to as positive deviance. This thesis examines positive behaviors, in the form of altruism, in the top 10 box-office animated movies of all time. Historically, studies focusing on negative, violent, and criminal behaviors garner much attention. Media violence is targeted as a cause for increasing violence, aggression, and antisocial behavior in youth; thousands of studies demonstrate that media violence especially influences children, a vulnerable group. Virtually no studies address the use of positive deviance in children’s movies. Using quantitative and ethnographic analysis, this paper yields three important findings. 1. Positive behaviors, in the form of altruism, are liberally displayed in children’s animated movies. 2. Altruism does not align perfectly with group loyalty. 3. Risk of life is used as a tool to portray altruism and is portrayed at critical, climactic, and memorable moments, specifically as movies draw to conclusion. Previous studies demonstrate that children are especially susceptible to both negativity and optimistic biases, underscoring the importance of messages portrayed in children’s movies. This study recommends that scholars and moviemakers consciously address the appearance and timing of positive deviance.
Keywords: Positive deviance; Altruism; Animation; Deviance; Sociology, General (0626)